RESETTLEMENT OF THE ORANG ASLI AND DEVELOPMENT PLAN FOR ORANG ASLI COMMUNITY IN MALAYSIA - Syed Hussain, Tuan Pah Rokiah; S. Krishnasamy, Devamany; Golam Hassan, Asan Ali (Journal of Techno-Social, 2017)
This article discusses the concept of Orang Asli used in the Malaysian Law under the Orang Asli Act 1954 (Act 134) that defines specifically to "any person whose male parent is or was, a member of an aboriginal ethnic group, who speaks an aboriginal language and habitually follows an aboriginal way of life and aboriginal customs and beliefs, and includes a descendant through males of such persons." The Orang Asli community till today is underdeveloped in many aspects namely economy, social and professional. To facilitate improvement to these problems and issues, the government implemented various programmes. The varied programmes include personality development to resettlement in order to improve the living standards of this community. This article discusses the programmes for the Orang Asli minority implemented to elevate them towards the desired national sustainable development levels.